2011
DOI: 10.1162/jocn_a_00042
|View full text |Cite
|
Sign up to set email alerts
|

Mine and Me: Exploring the Neural Basis of Object Ownership

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Using fMRI, the current study explored the neural correlates of object ownership. During scanning, participants sorted everyday objects into self-owned or other-owned categories. Replicating previous research, a significant self-memory advantage for the objects was observed (i.e., sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 71 publications
(89 reference statements)
2
58
0
2
Order By: Relevance
“…The self is generally understood to operate through multiple routes, enhancing memory through increased attention and arousal (hence increased task engagement), but also by providing a familiar, easily accessible construct through which incoming information can be elaborated and organised (Klein & Kihlstom, 1986, Klein & Loftus, 1988Symons & Johnson, 1997Turk, van Bussel, Brebner et al, 2011;Turk, van Bussel, Waiter et al, 2011), giving rise to rich, recollective retrieval from memory (Van den Bos, Cunningham, Conway & Turk, 2010). In this regard, the self is not regarded as providing a 'special' route to enhanced encoding, although it may be especially efficient at eliciting these multiple routes (see Gillihan & Farah, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The self is generally understood to operate through multiple routes, enhancing memory through increased attention and arousal (hence increased task engagement), but also by providing a familiar, easily accessible construct through which incoming information can be elaborated and organised (Klein & Kihlstom, 1986, Klein & Loftus, 1988Symons & Johnson, 1997Turk, van Bussel, Brebner et al, 2011;Turk, van Bussel, Waiter et al, 2011), giving rise to rich, recollective retrieval from memory (Van den Bos, Cunningham, Conway & Turk, 2010). In this regard, the self is not regarded as providing a 'special' route to enhanced encoding, although it may be especially efficient at eliciting these multiple routes (see Gillihan & Farah, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a linear relationship between writing performance and spelling accuracy suggests that spelling improvements are not produced by increased engagement alone. Previous research has indicated that self-relevant encoding tasks increase attentional processing and affective arousal (Bargh, 1982;Turk, van Bussel, Brebner et al, 2011), supporting memory increases for words and objects associated with self Turk, van Bussel, Waiter & Macrae, 2011). These low-level mechanisms may play an important role in increasing educational performance, especially in literacy tasks like spelling traditionally thought of as "boring" by a significant minority of children (Scottish Survey of Achievement: Reading and Writing 2009).…”
Section: Participant B Aged 104 Mthsmentioning
confidence: 97%
“…Recent research has also examined the effect of ownership on product-self associations for new products that are randomly assigned to be owned, actually or psychologically (Turk et al 2011). This research shows that people more readily recall objects they were randomly assigned to own, presumably because ownership associates the product to the self, and encoding an item with respect to the self makes the item more memorable (Rogers et al 1977).…”
Section: Flowchart Of the Theoretical Modelmentioning
confidence: 99%
“…People have better memory for goods that they own than goods that are owned by others, even if that ownership is simply imagined [85][86][87]. This memory bias is correlated with the activation and deactivation of brain regions involved in self-referential processing while thinking about who owns those goods [68,88].…”
Section: Psychological Ownershipmentioning
confidence: 99%